EXPLORATION OF TRADITIONAL FISHERMEN'S INCOME IN KRUEN MANE, NORTH ACEH REGENCY - Muttaqien; Wardiah; Muhammad Hafizh; Frengki Putra Ramansyah; Cut Zira Maulida (International Conference on Health Science, Green Economics, Educational Review and Technology, 2024)
Fishermen's income is an accumulation of the results of fishermen's efforts that do not stand alone, but are influenced by various factors. Therefore, fishermen's income such as capital, season, climate, fishing gear productivity, fishing areas, fish prices and the amount of fish caught.Fishermen's income factors include factors such as seasonal fluctuations, limited capital and human resources, access to exploitative fish trade networks, and the negative effects of fisheries modernization and the blue revolution, both of which have led to excessive depletion of marine resources. This process is still ongoing today, and fishermen are experiencing further impacts from declining income levels and difficulties in obtaining their catches. The purpose of this study is to determinemetThe revenue analysis method that calculates fixed costs and variable costs to revenue. Furthermore, a production function analysis is carried out, where the production function describes the relationship between input and output. Based on this, the results of this studyexpected to be a consideration for the government in formulating policies related to the welfare of traditional fishermen with all their limitations. This type of research is quantitative descriptive with a research population of traditional fishermen in Krueng Mane, North Aceh. The type of data in this study uses primary data in the form of a questionnaire with a Likert scale where the selection of research samples uses random sampling which will then be subjected to regression using the SPSS application.